2000
DOI: 10.1385/bter:74:3:245
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Image and Blood Manganese Concentration as Indices for Manganese Content in the Brain of Rats

Abstract: Neurological disorders similar to parkinsonian syndrome and signal hyperintensity in brain on T1-weighted magnetic resonance (MR) images have been reported in patients receiving long-term total parenteral nutrition (TPN). These symptoms have been associated with manganese (Mn) depositions in brain. Although alterations of signal intensity on T1-weighted MR images in brain and of Mn concentration in blood are theoretically considered good indices for estimating Mn deposition in brain, precise correlations betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Of the 46 included papers, 40 studied iron [1-3, 5, 7, 15-50], 3 studied calcium [28,36,51], 1 studied copper [36] and 6 studied manganese [36,[52][53][54][55][56] deposition (see Table in the Electronic Supplementary Material).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 46 included papers, 40 studied iron [1-3, 5, 7, 15-50], 3 studied calcium [28,36,51], 1 studied copper [36] and 6 studied manganese [36,[52][53][54][55][56] deposition (see Table in the Electronic Supplementary Material).…”
Section: Resultsmentioning
confidence: 99%
“…We only found one study that confirmed histologically the MRI appearance of copper in four human brains as hyperintense on T1W and hypointense on T2W images [36]. Manganese was imaged at 4.7 T [53-56] and 1.5 T [52] in rodents and at 0.5 T and 1.5 T [33] in humans. In all cases the manganese was reported as hyperintense on T1W images.…”
Section: Calcium Deposits In the Brainmentioning
confidence: 96%
See 1 more Smart Citation
“…In an in vitro study using manganese and trace element (iron, copper, zinc, and iodine) solutions diluted with physiologic saline or rat brain homogenate, Chaki et al (12) observed concentration-dependent signal hyperintensity only for the solutions that contained manganese; no effect was observed for solution without manganese. The same team also reported that certain brain sites in rats that received TPN showed a strong positive correlation between whole-blood manganese concentrations and the signal intensity on T 1 -weighted images (13). Thus, the general consensus is that during parenteral nutrition, T 1 shortening is due to manganese accumulation.…”
Section: Discussionmentioning
confidence: 96%
“…Two research groups reported studies on the determination of Mn in blood or tissues of rats and mice following administration of Mn compounds. Chaki et al 168 used AAS to determine Mn concentrations in blood and brain tissue of rats receiving total parenteral nutrition (TPN) with an elevated trace element content. The authors also used magnetic resonance imaging to examine signal hyperintensity in the brain.…”
Section: 918mentioning
confidence: 99%